Proceedings of the 2022 Conference of the North American Chapter of the Association for Computational Linguistics: Human Langua 2022
DOI: 10.18653/v1/2022.naacl-main.114
|View full text |Cite
|
Sign up to set email alerts
|

Same Neurons, Different Languages: Probing Morphosyntax in Multilingual Pre-trained Models

Abstract: The success of multilingual pre-trained models is underpinned by their ability to learn representations shared by multiple languages even in absence of any explicit supervision. However, it remains unclear how these models learn to generalise across languages. In this work, we conjecture that multilingual pretrained models can derive language-universal abstractions about grammar. In particular, we investigate whether morphosyntactic information is encoded in the same subset of neurons in different languages. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
2
7
0
Order By: Relevance
“…We speculate that this low number of values leads to low variation among languages, thus the non-significant difference. This finding concurs with Stanczak et al (2022), who observed a negative correlation between the number of values per morphosyntactic category and the proportion of language pairs with significant neuron overlap. Hence, the lack of significant differences in variance between the diverse and related sets can be attributed to the substantial overlap of neurons across language pairs.…”
Section: Language Proximity and Low-resource Conditionssupporting
confidence: 91%
See 3 more Smart Citations
“…We speculate that this low number of values leads to low variation among languages, thus the non-significant difference. This finding concurs with Stanczak et al (2022), who observed a negative correlation between the number of values per morphosyntactic category and the proportion of language pairs with significant neuron overlap. Hence, the lack of significant differences in variance between the diverse and related sets can be attributed to the substantial overlap of neurons across language pairs.…”
Section: Language Proximity and Low-resource Conditionssupporting
confidence: 91%
“…This observation holds true for all categories, with the exception of Animacy, which is predominantly found in Slavic languages within our dataset. This aligns with the findings of Stanczak et al (2022), who noted that the correlation analysis results can be affected by whether a category is typical for a specific genus. Next, we further explore the relationship between signature values and language properties.…”
Section: Logogram Vs Phonogramsupporting
confidence: 90%
See 2 more Smart Citations
“…Particularly, they proposed to rank frozen encoder representations by determining the percentage of trees that are recoverable from them, and based on that ranking choose which LLM to plug. Focused on morphology, Stanczak et al (2022) showed that subsets of neurons model morphosyntax across a variety of languages in multilingual LLMs.…”
Section: Related Workmentioning
confidence: 99%